2021
DOI: 10.48550/arxiv.2110.10159
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Orders of Vanishing and U(1) Charges in F-theory

Nikhil Raghuram,
Andrew P. Turner

Abstract: Many interesting questions about F-theory models, including several concerning the F-theory swampland, involve massless matter charged under U(1) gauge symmetries. It is therefore important to better understand the geometric properties of F-theory models realizing various U(1) charges. We propose that, for F-theory models described by elliptic fibrations in Weierstrass form, the U(1) charge of light matter is encoded in the orders of vanishing of the section components corresponding to the U(1) gauge symmetry.… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 71 publications
(238 reference statements)
0
2
0
Order By: Relevance
“…They showed in [24] that for 6D F-theory models, the property of charge completeness 1 Reviews of the swampland criteria can be found in [4,5]. 2 Recent studies have investigated gauge groups formed in F-theory, for example [9,10,11,12,13,14,15,16,17,18,19,20,21,22,23,24,25]. 3 The notion of the charge completeness was discussed by the authors in [26].…”
Section: Introductionmentioning
confidence: 99%
“…They showed in [24] that for 6D F-theory models, the property of charge completeness 1 Reviews of the swampland criteria can be found in [4,5]. 2 Recent studies have investigated gauge groups formed in F-theory, for example [9,10,11,12,13,14,15,16,17,18,19,20,21,22,23,24,25]. 3 The notion of the charge completeness was discussed by the authors in [26].…”
Section: Introductionmentioning
confidence: 99%
“…The field has been intensively studied since this progress, e.g., in[17,18,19,20,21,22,23,24,25,26,27,28,29,30,31,32,33,34,35,36,37,38,39,40] 2. There have been various efforts to analyze gauge groups formed in F-theory, e.g., in[45,46,47,48,49,50,51,52,53,54,55,56,57].…”
mentioning
confidence: 99%